Model Tarbiyah Digital: Pendidikan Anak dalam Perspektif Al-Qur’an dan Hadits di Era Kekerasan Online - Debi Tiara Wulan Dari; Siti Rahmatullisa; Ali Imron; Mukmin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Child education in Islamic perspective is an integrated process aimed at developing individuals with strong faith, noble character, and social responsibility. The rapid growth of digital technology presents both opportunities and critical challenges for children’s character development, particularly due to the increasing prevalence of deviant behaviors, online violence, and moral degradation. Recent data from UNICEF, KPAI, and the Ministry of Women and Children’s Empowerment of Indonesia reveal a significant rise in cyberbullying, digital-based sexual exploitation, and gadget addiction over the past five years, which negatively affect mental health, social empathy, and religious commitment. This study employs a descriptive qualitative approach through library research and tarbawi interpretation of Qur’anic verses, specifically Surah Luqman 13-19, to identify educational values relevant to the digital era. The findings show that these verses contain comprehensive educational principles including monotheism, spiritual consciousness (muraqabah), habitual worship, enjoining good and forbidding evil, emotional regulation, and ethical communication. These values play a crucial role in strengthening internal self-control as a moral shield against the destructive impact of technology. The integration of family and school-based Islamic education through the Islamic Digital Tarbiyah Model offers an applicable approach for educating digitally literate, morally upright, and spiritually grounded generations. The study concludes that Islamic education holds a strategic position in balancing technological development with spiritual and moral formation.